Overcoming mental fatigue through mindfulness: improving physical and cognitive performance in elite handball players - Staiano, W.; Sternberg, L. M.; Ferri-Caruana, A.; Salazar Bonet, L.; Romagnoli, M.; Henriksen, K.; Kirk, U. (Journal of Science and Medicine in Sport, 2025)
Objectives Empirical evidence that mindfulness buffers elite athletes against mental-fatigue decrements remains sparse. This trial examined whether a six-week mindfulness-based intervention (MBI) augments cognitive and sport-specific physical performance in elite handball players in fresh and mentally fatigued states.